Fibre optic fizeau intererometer for optical coherence tomography - Casaubieilh, P. (Cranfield University, 2006)
The aim of the project was to develop the Fizeau interferometer configuration to take advantage of the benefits derived from its “downlead insensitivity” to temperature and polarisation fading. This sensing interferometer was investigated and implemented in conjunction with various processing interferometers with the view to achieve optimised performances for Optical Coherence Tomography (OCT) application. A comprehensive theoretical analysis has been carried for Signal-to-Noise ratio of these OCT systems. Balanced detection indenting two detectors with anti-phase signals was also investigated to improve further the SNR. The analysis showed that the SNR (67 dB) of the balanced Fizeau interferometer improved by 30 dB from that of standard Fizeau interferometer implementing a single detector. Experimentally, the best SNR for this configuration was achieved by adding an electronic rectifier based demodulation system for the signal after balanced detection. The OCT systems investigated in this project were developed based on a broadband source operating in the 1550 nm wavelength-band to facilitate improvement in the depth of penetration of light directed into imaged samples. The coherence length or axial resolution in air of the system was 21[micro milli]while the transverse resolution was 18 [micro milli] and focusing depth was 340 [micro milli].